Body composition and nutritional status of the Spanish national breaking team aspiring to the Paris 2024 Olympic Games - Montalbán-Méndez, C.; Giménez-Blasi, N.; García-Rodríguez, I. A.; Latorre, J. A.; Conde-Pipo, J.; López-Moro, A.; Mariscal-Arcas, M.; Gil-Antuñano, N. P. (Nutrients, 2023)
Breaking is a sports dance modality that will debut for the first time at the Paris 2024 Olympic Games. This dance form combines street dance steps with acrobatics and athletic elements. It complies with gender equality, maintains aesthetic appeal, and is practised indoors. The objective of this study is to assess the characteristics of body composition and nutritional status of the athletes that make up the Breaking national team. This national team was recruited, and they underwent an analysis of body composition using bioimpedance measurement and a nutritional interview status with the completion of a survey on the frequency of the consumption of sports supplements and ergogenic aids. In addition, they completed a consumption questionnaire for a series of food groups with specified protein, lipid, and carbohydrate content. After that, parameters were analyzed in relation to their nutritional status during a complete medical examination at the Endocrinology and Nutrition Service of the Sports Medicine Center of CSD. A descriptive analysis of the results obtained was carried out to find the mean values of the variables analyzed. The analytical parameters described an adequate nutritional status, except for the mean capillary determination of 25-OH-vitamin D3, which was 24.2 ng/dL (SD: 10.3). Bone mineral density values were higher than those of the general population. This is the first time that a study of these characteristics has been carried out on Breakers, so it is highly relevant to increase knowledge in this area in order to conduct nutritional interventions aimed at improving the sports performance of these athletes.